Staatliche Förderung beruflicher Weiterbildung in Deutschland und Schweden Strukturen der Einbindung Dritter bei der Förderung beruflicher Weiterbildungsmaßnahmen - Meeßen, Iris (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2017)
"The state supports lifelong learning and, in doing so, not only promotes economic objectives but, above all, also objectives in terms of social law. Both Germany and Sweden promote further education programmes by means of cash benefits and benefits in kind. The promoted further education programmes in this context are largely provided by third parties, much like many other social services. For this purpose, an actual framework and certain legal structures are essential, and these are often competitive structures, given the fact that the system of further education has evolved historically. It is not necessarily so that the objective of the educational measure supported by a specific benefit is attained as intended. The purpose of the examination is therefore to find out how the state ensures fulfilment of the objectives of the supporting measures. In order to determine whether this is the case particularly with regard to the provision of services by third parties, the two legal systems are compared."